1975
DOI: 10.1111/j.1432-1033.1975.tb02264.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Distribution of Neutral Proteinases and Inhibitors in Pig Leucocytes. Isolation of Two Inhibitors of Neutral Proteinases

Abstract: Granule and post-granular-supernatant fractions were obtained from pig leucocyte cells by differential centrifugation in 0.34 M sucrose.Granule extract possesses proteinase activity at acid and at neutral pH. Three groups of neutral and a group of acid proteinases were isolated from granule extracts by chromatography on DEAEcellulose. In the first group are present elastase-like and plasminogen-activator proteinases, that are inhibited by diisopropylphosphorofluoridate, a,-antitrypsin, intracellular leucocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1976
1976
1991
1991

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…The granule fraction contained a neutral protease capable of attacking the telopeptide regions in fluorescein-labelled polymeric collagen fibrils, confirming earlier reports [1,2]. When 100 pl of the granule extract was incubated with the fluorescent substrate in the presence of increasing quantities of the postgranule supernatant fraction for 1.5 h (Fig.…”
Section: The Neutral Protease and Its Inhibitionsupporting
confidence: 71%
“…The granule fraction contained a neutral protease capable of attacking the telopeptide regions in fluorescein-labelled polymeric collagen fibrils, confirming earlier reports [1,2]. When 100 pl of the granule extract was incubated with the fluorescent substrate in the presence of increasing quantities of the postgranule supernatant fraction for 1.5 h (Fig.…”
Section: The Neutral Protease and Its Inhibitionsupporting
confidence: 71%
“…Preliminary observations suggested that the cytosol of neutrophils contains inhibitors of the collagenolytic activity of granule extracts (Kopitar & Lebez, 1975);…”
mentioning
confidence: 99%
“…Leucocytes were isolated from pig blood (5,400 ml), as described previously (17). The cells were suspended in 0.34 M sucrose and homogenized with a Teflon pestle.…”
Section: Extraction and Fractionation O F Leucocyte Nuclei Componentsmentioning
confidence: 99%
“…In the course of our continuing studies, two types of specific inhibi tors of proteinases were isolated from pig leucocytes and from bovine spleen. These inhibitors are acidic proteins (Ip 4.6-5.6) and differ in molecular weight, inhibitory ability against tested enzymes and immunologically (4,(17)(18)(19)(20)(21). Neither Inhibitor-1 (1-1) nor Inhibitor-2 (1-2) inhibits trypsin or urokinase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation